Identification of Potential anti-dengue lead from Nilavembu through in silico study (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Dengue fever is a severe mosquito-borne global health concern caused by the Dengue virus. There are no effective vaccines or anti-virals against dengue, even though several medications are under developmental stages. As we all know, the traditional medicine system mainly depends on plants to treat various types of diseases caused by bacteria, viruses, and other micro-organisms. In this scenario, the present study focussed on identifying the inhibitory potential of phytoconstituents from a well-known antipyretic medicinal herb Andrographis paniculata (Burm.f.) Nees against MTase domain of NS5 protein from the virus and IMPDH2 from the host through Molecular docking to identify the hit compounds and further drug-likeness, pharmacokinetics, and toxicity studies were carried out to ascertain a lead candidate. Through molecular interaction results, it was identified that in the case of NS5, about 28 compounds showed the least binding energy than native ligand SAH and were recommended as hits, out of which 12 compounds interact specifically with the active site residues and were selected as top hits. In the case of IMPDH2, 13 compounds were identified as hits since they showed less binding energy than native ligand RVP, and among that, nine compounds were selected as top hits based on their interaction with the active site residues. Furthermore, the selected hit molecules were subjected to drug-likeness, pharmacokinetics, and toxicity prediction and identified Oleanolic acid as the best lead candidate against both the targets NS5 and IMPDH-II. The study further emphasizes Oleanolic acid as the best lead candidate because naturally, triterpenoid compounds possess anti-viral activity but further in vitro and in vivo studies are essential to propose Oleanolic acid as an anti-dengue compound.